2022
DOI: 10.1128/spectrum.01068-22
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Integration Reveals the Crucial Role of Fusobacterium in the Inflammatory Immune Microenvironment in Head and Neck Squamous Cell Carcinoma

Abstract: Studies on revealing the composition and potential mechanisms of the tumor microbiome are still at an initial stage. We uncovered the potential contribution of the tumor-resident microbiota on the immunosuppressive microenvironment in HNSC, which will provide a new perspective for tumor microbiome research and yield valuable insights into the clinical management of HNSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Furthermore, the disturbance of the oral microbiome may indirectly promote the occurrence and development of cancers by causing persistent chronic inflammation and suppressing immune response [ 50 , 51 ]. Several studies have shown that the periodontal pathogen Fusobacterium nucleatum might increase the risk of head and neck cancers by indirect carcinogenic effects [ 52 , 53 ]. A recent study revealed that CD8 + T infiltration was decreased in NPC tumor tissues with high bacterial load, indicating that the microbiome may influence NPC by modulating the immune microenvironment [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the disturbance of the oral microbiome may indirectly promote the occurrence and development of cancers by causing persistent chronic inflammation and suppressing immune response [ 50 , 51 ]. Several studies have shown that the periodontal pathogen Fusobacterium nucleatum might increase the risk of head and neck cancers by indirect carcinogenic effects [ 52 , 53 ]. A recent study revealed that CD8 + T infiltration was decreased in NPC tumor tissues with high bacterial load, indicating that the microbiome may influence NPC by modulating the immune microenvironment [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…SH2 domain containing 5, and solute carrier family 31 member 2. 25 These genes exert chronic inflammatory effects through the increased activation of NF-κB and inflammation, cell-cell adhesion, and other pathways, resulting in an immunosuppressive TME. 25…”
Section: Itm Reshapes the Tme For Tumor Developmentmentioning
confidence: 99%
“…In head and neck squamous cell carcinoma, the enrichment of Clostridium spp. is positively associated with inflammatory genes, including epiregulin, proline rich and Gla domain 1, SH2 domain containing 5, and solute carrier family 31 member 2 25 . These genes exert chronic inflammatory effects through the increased activation of NF‐κB and inflammation, cell‐cell adhesion, and other pathways, resulting in an immunosuppressive TME 25 .…”
Section: Interplay Between Itm and The Tme In Tumor Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…There are multiple reports describing the microbiota in HNSC [26][27][28]. Most of these studies compared the microbiota diversity and bacterial relative abundance between cancer and healthy samples using 16S ribosomal RNA (rRNA) sequencing [26][27][28], while two studies additionally correlated the impact of the microbiota with matched transcriptome analysis [29,30]. Samples studied include tissues, swabs and oral fluids (saliva or oral rinse) from cancer and healthy patients.…”
Section: Introductionmentioning
confidence: 99%